Gray cast iron composite material

By combining chopped carbon fiber with gray cast iron material to form a composite material, the problem of low hardness and strength of gray cast iron material is solved, and the material performance is significantly improved, which is suitable for a variety of application scenarios.

CN119710500AInactive Publication Date: 2025-03-28JIANGSU ZHONGXIN FOUNDRY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311244619.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing gray cast iron materials have low hardness and strength, limiting their expansion in production and use.

Method used

A chopped carbon fiber with a length of 1 mm to 3 mm is used to form a composite material and gray cast iron material. Through the enhanced performance of carbon fiber and the refinement effect during solidification, the hardness and strength of the material are improved.

Benefits of technology

It significantly improves the hardness and strength of gray cast iron composite materials, enhances its wear resistance, corrosion resistance and impact performance, and is suitable for the production of thin-walled gray cast iron parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of gray cast iron, and discloses a gray cast iron composite material, the gray cast iron carbon fiber composite material is composed of surface-glued or glue-free chopped carbon fibers with the length of 1-3 mm and a gray cast iron material, furnace charge is prepared from 30-38% of pig iron, 25-34% of foundry returns, 30-38% of scrap steel, 0-1% of silicon iron, 0.2-1.2% of ferromanganese and 0.8-1.4% of recarburized graphite, and the furnace charge is prepared into the gray cast iron components including 3.1-3.6% of carbon, 1.5-2.2% of silicon, 1.5-2.2% of iron and the balance iron. 0.3%-1.0% of manganese, and 1t of phosphorus; the content of sullt is 0.02%; 0.1%, and the balance being iron. According to the gray cast iron composite material, the carbon fibers and the gray cast iron form the gray cast iron composite material, the carbon fibers play a role in enhancing performance in the gray cast iron material and play a role in refining flake graphite in the gray cast iron solidification process, and the wear resistance of the carbon fibers can improve the wear resistance of the gray cast iron; the carbon fibers are added into the gray cast iron, so that the gray cast iron cannot be abraded and broken in the long-time use process, the corrosion resistance of the gray cast iron can be improved through the corrosion resistance of the carbon fibers, the gray cast iron cannot be corroded and rusted in a severe environment, and the carbon fibers are suitable for producing thin-wall gray cast iron parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grey cast iron, in particular to a grey cast iron composite material. Background Art

[0002] In casting production, cast iron production accounts for 70%. Due to its excellent casting performance, high yield rate, good vibration reduction performance and low production cost, the output of gray cast iron is the highest among all kinds of cast iron. However, the strength of graphite in gray cast iron is very low. Graphite is equivalent to holes in the cast iron structure, which greatly affects the strength of cast iron. Therefore, improving the strength of gray cast iron is of great significance to the expansion of the production and use of gray cast iron.

[0003] Although carbon fiber and graphite are both carbon materials, the arrangement of their carbon atoms is different. Carbon fiber is a special fiber composed of carbon elements, which has the characteristics of high temperature resistance (heat resistance temperature greater than 2000℃), anti-friction, electrical conductivity, thermal conductivity and corrosion resistance. It is fibrous, soft, and can be made into various fabric materials. Because its graphite microcrystalline structure is preferentially oriented along the fiber axis, it has high strength (5 times that of steel) and modulus along the fiber axis. Carbon fiber has a low density, so it has high specific strength and specific modulus. At present, the main use of carbon fiber is as a reinforcing material to be compounded with resin, metal, ceramic and carbon to manufacture advanced composite materials. It has not been used in gray cast iron materials. For this reason, we propose a gray cast iron composite material. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a grey cast iron composite material having the advantages of enhancing material properties and refining flake graphite during the solidification process of grey cast iron, thereby solving the problem of low hardness and strength of the prior art materials.

[0005] In order to achieve the above-mentioned performance of the reinforcing material and to play a role in refining flake graphite during the solidification process of gray cast iron, the present invention provides the following technical solution: a gray cast iron composite material, comprising short carbon fibers with a length of 1 mm to 3 mm and a surface coated with glue or without glue and a gray cast iron material to form a gray cast iron carbon fiber composite material, and the charge composition is as follows: Pig iron 30~38% 25~34% recycled materials Scrap steel 30~38% Ferrosilicon 0~1% Ferromanganese 0.2~1.2% Carbon-reinforced graphite 0.8~1.4%; The above charge is prepared into gray cast iron, and its composition is as follows: Carbon 3.1~3.6% Silicon 1.5~2.2% Manganese 0.3~1.0% Phosphorus <0.02%, sulfur <0.1%, and the balance is iron.

[0006] Preferably, the preparation steps are as follows: Step 1, add the above-mentioned charge into the induction furnace for smelting according to the smelting process requirements, add carbon-enhanced graphite to the bottom of the furnace in sequence, add slag-making agent, add 30% of pig iron, add scrap steel, and gradually add 70% of pig iron after melting. When the temperature of the molten metal rises to 1450-1480°C, add ferromanganese first and then ferrosilicon to deoxidize and increase the manganese and silicon content of the molten metal; Step 2: Add 0.3-0.5% of the weight of the inoculant to the above-mentioned molten metal, and remove the slag after standing in the ladle for 2-3 minutes. The inoculant is a ferrosilicon inoculant with a silicon content of 75% and a particle size of 15-20 mm. Step 3: Pour the molten metal in the ladle into the ladle in batches and perform secondary inoculation treatment. The inoculant is a ferrosilicon inoculant with a silicon content of 75%, a particle size of 1-2 mm, and an addition amount of 0.08-0.1% of the weight of the molten metal; Step 4: Place 0.4% to 1.5% of the weight of the casting into the pouring cup of the casting mold; Step 5: During the pouring process of the molten metal, the carbon fiber flows into the mold cavity along with the molten metal and mixes with the molten metal; Step 6: When the molten metal solidifies in the mold and cools to below 300-400°C, open the box and clean the sand.

[0007] Preferably, the pouring temperature of the molten metal in step five is 1380-1410°C.

[0008] Preferably, the charge composition is: 35% pig iron, 25-34% recycled material, 35% scrap steel, 0.2% ferrosilicon, 0.8% ferromanganese and 1.2% carbon-reinforced graphite.

[0009] Preferably, the charge is formulated into a grey cast iron composition of: 3.20% carbon, 1.13% silicon, 0.98% manganese, 0.017% phosphorus and 0.065% sulfur, with the balance being iron.

[0010] Preferably, 0.5% of the weight of the inoculant is added to the molten metal along with the flow, and the slag is removed after standing in the ladle for 3 minutes. The inoculant is a ferrosilicon inoculant with a silicon content of 75% and the remainder being iron, and the particle size is 15 mm.

[0011] Preferably, the molten metal in the ladle is poured into the casting ladle in batches and subjected to secondary inoculation treatment. The inoculant is a ferrosilicon inoculant containing 75% silicon and the remainder iron, with a particle size of 1.5 mm and an addition amount of 0.1% of the weight of the molten metal.

[0012] Preferably, the chopped carbon fibers placed in the pouring cup of the casting are 1% by weight of the casting.

[0013] Preferably, the pouring temperature of the molten metal is 1390°C.

[0014] Preferably, the grey cast iron has a tensile strength of 297 MPa.

[0015] Compared with the prior art, the present invention provides a gray cast iron composite material, which has the following beneficial effects: 1. The present invention adopts carbon fiber and gray cast iron to form a gray cast iron composite material. The carbon fiber plays a role in enhancing the performance of the gray cast iron material and in refining the flake graphite during the solidification process of the gray cast iron, thereby improving the hardness and strength of the gray cast iron composite material. The wear resistance of the carbon fiber can improve the wear resistance of the gray cast iron, so that it will not wear and break during long-term use. The corrosion resistance of the carbon fiber can improve the corrosion resistance of the gray cast iron, so that it will not corrode and rust in harsh environments, and is suitable for the production of thin-walled gray cast iron parts.

[0016] 2. The present invention adopts carbon fiber and gray cast iron to form a gray cast iron composite material. The impact performance of carbon fiber can improve the impact performance of gray cast iron, so that it can withstand greater impact and stress.

[0017] 3. The present invention adopts carbon fiber and gray cast iron to form a gray cast iron composite material. The carbon fiber has good electrical insulation performance, which can improve the electrical insulation performance of gray cast iron and prevent electromagnetic induction from damaging the gray cast iron. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the preparation process of the present invention; Figure 2 This is a metallographic diagram of a cross section of type A graphite of the present invention; Figure 3 This is a metallographic diagram of the cross section of type A graphite of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Carbon fiber is a high-performance fiber used to make composite materials. It has extremely high mechanical strength, which is higher than most metal-based composite materials. This is due to its high specific surface area and low density, which enables carbon fiber to withstand a high stress modulus when subjected to stress. At the same time, carbon fiber has good fatigue resistance and can withstand a large amount of cyclic stress without cracking and fatigue damage. Carbon fiber has very good wear resistance, which is better than many metal-based composite materials and can also improve the wear resistance of composite materials.

[0021] The present invention combines carbon fiber and gray cast iron to form a gray cast iron composite material, so as to improve the performance of the composite material.

[0022] A gray cast iron composite material, comprising short carbon fibers with a length of 1 mm to 3 mm and coated with glue or without glue on the surface and a gray cast iron material to form a gray cast iron carbon fiber composite material, wherein the charge composition is as follows: Pig iron 30~38% 25~34% recycled materials Scrap steel 30~38% Ferrosilicon 0~1% Ferromanganese 0.2~1.2% Carbon-reinforced graphite 0.8~1.4%; The above charge is prepared into gray cast iron, and its composition is as follows: Carbon 3.1~3.6% Silicon 1.5~2.2% Manganese 0.3~1.0% Phosphorus <0.02%, sulfur <0.1%, and the balance is iron.

[0023] The present invention adopts carbon fiber and gray cast iron to form a gray cast iron composite material. The carbon fiber plays a role of enhancing the performance in the gray cast iron material and refining flaky graphite during the solidification process of the gray cast iron, thereby improving the hardness and strength of the gray cast iron composite material. The wear resistance of the carbon fiber can improve the wear resistance of the gray cast iron, so that it will not wear and break during long-term use. The corrosion resistance of the carbon fiber can improve the corrosion resistance of the gray cast iron, so that it will not corrode and rust in harsh environments, and is suitable for the production of thin-walled gray cast iron parts. The impact performance of the carbon fiber can also improve the impact performance of the gray cast iron, so that it can withstand greater impact and stress. At the same time, the carbon fiber has good electrical insulation performance, which can improve the electrical insulation performance of the gray cast iron and prevent electromagnetic induction from damaging the gray cast iron.

[0024] See also Figure 1 , the preparation steps are as follows: Step 1, add the above-mentioned charge into the induction furnace for smelting according to the smelting process requirements, add carbon-enhanced graphite to the bottom of the furnace in sequence, add slag-making agent, add 30% of pig iron, add scrap steel, and gradually add 70% of pig iron after melting. When the temperature of the molten metal rises to 1450-1480°C, add ferromanganese first and then ferrosilicon to deoxidize and increase the manganese and silicon content of the molten metal; Step 2: Add 0.3-0.5% of the weight of the inoculant to the above-mentioned molten metal, and remove the slag after standing in the ladle for 2-3 minutes. The inoculant is a ferrosilicon inoculant with a silicon content of 75% and a particle size of 15-20 mm. Step 3: Pour the molten metal in the ladle into the ladle in batches and perform secondary inoculation treatment. The inoculant is a ferrosilicon inoculant with a silicon content of 75%, a particle size of 1-2 mm, and an addition amount of 0.08-0.1% of the weight of the molten metal; Step 4: Place 0.4% to 1.5% of the weight of the casting into the pouring cup of the casting mold; Step 5: During the pouring process of the molten metal, the carbon fiber flows into the mold cavity along with the molten metal and mixes with the molten metal; Step 6: When the molten metal solidifies in the mold and cools to below 300-400°C, open the box and clean the sand.

[0025] The following are examples of specific numerical values: 1. Charge composition: 35% pig iron, 27.8% recycled material, 35% scrap steel, 0.2% ferrosilicon, 0.8% ferromanganese and 1.2% carbon-reinforced graphite.

[0026] 2. The above charge is prepared into gray cast iron with the following composition: carbon 3.20%, silicon 1.13%, manganese 0.98%, phosphorus 0.017%, sulfur 0.065%, and the balance is iron.

[0027] 3. Add the above charges into the induction furnace for smelting according to the smelting process requirements. The process requirements are: add carbon-enhanced graphite to the bottom of the furnace, add slag-making agent, add 30% pig iron, add scrap steel, and gradually add 70% pig iron after melting. When the temperature of the molten metal rises to 1480°C, add ferromanganese first and then ferrosilicon to deoxidize and increase the manganese and silicon content of the molten metal.

[0028] 4. Add 0.5% of the weight of the inoculant to the above-mentioned molten metal, and remove the slag after standing in the ladle for 3 minutes. The inoculant is a ferrosilicon inoculant with a silicon content of 75% and the balance being iron, and a particle size of 15 mm.

[0029] 5. Pour the molten metal in the ladle into the casting ladle in batches and carry out secondary inoculation treatment. The inoculant is a ferrosilicon inoculant with a silicon content of 75% and the balance being iron, with a particle size of 1.5 mm and an addition amount of 0.1% of the weight of the molten metal.

[0030] 6. Place 1% of the casting weight of chopped carbon fiber into the pouring cup of the casting mold.

[0031] 7. During the pouring process of molten metal, the carbon fiber flows into the mold cavity along with the molten metal and mixes with the molten metal.

[0032] 7. When the molten metal solidifies in the mold and cools to below 300~400℃, open the box and clean the sand.

[0033] 9. The pouring temperature of molten metal is 1390℃.

[0034] 10.The tensile strength of gray cast iron is 297MPa.

[0035] 11. Metallographic diagram of composite materials Figure 2 , Figure 3 , the figure shows A-type graphite, which has no directionality.

[0036] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A grey cast iron composite material, characterized in that: The short carbon fiber with a length of 1 mm to 3 mm and the surface coated with glue or without glue are combined with the gray cast iron material to form a gray cast iron carbon fiber composite material. The composition of the charge is as follows: Pig iron 30~38% 25~34% recycled materials Scrap steel 30~38% Ferrosilicon 0~1% Ferromanganese 0.2~1.2% Carbon-reinforced graphite 0.8~1.4%; The above charge is prepared into gray cast iron, and its composition is as follows: Carbon 3.1~3.6% Silicon 1.5~2.2% Manganese 0.3~1.0% Phosphorus <0.02%, sulfur <0.1%, and the balance is iron.

2. The gray cast iron composite material according to claim 1, characterized in that: The preparation steps are as follows: Step 1, add the above-mentioned charge into the induction furnace for smelting according to the smelting process requirements, add carbon-enhanced graphite to the bottom of the furnace in sequence, add slag-making agent, add 30% of pig iron, add scrap steel, and gradually add 70% of pig iron after melting. When the temperature of the molten metal rises to 1450-1480°C, add ferromanganese first and then ferrosilicon to deoxidize and increase the manganese and silicon content of the molten metal; Step 2: Add 0.3-0.5% of the weight of the inoculant to the above-mentioned molten metal, and remove the slag after standing in the ladle for 2-3 minutes. The inoculant is a ferrosilicon inoculant with a silicon content of 75% and a particle size of 15-20 mm. Step 3: Pour the molten metal in the ladle into the ladle in batches and perform secondary inoculation treatment. The inoculant is a ferrosilicon inoculant with a silicon content of 75%, a particle size of 1-2 mm, and an addition amount of 0.08-0.1% of the weight of the molten metal; Step 4: Place 0.4% to 1.5% of the weight of the casting into the pouring cup of the casting mold; Step 5: During the pouring process of the molten metal, the carbon fiber flows into the mold cavity along with the molten metal and mixes with the molten metal; Step 6: When the molten metal solidifies in the mold and cools to below 300-400°C, open the box and clean the sand.

3. The gray cast iron composite material according to claim 2, characterized in that: The pouring temperature of the molten metal in step 5 is 1380-1410°C.

4. The gray cast iron composite material according to claim 3, characterized in that: The charge composition includes: 35% pig iron, 25-34% recycled materials, 35% scrap steel, 0.2% ferrosilicon, 0.8% ferromanganese and 1.2% carbon-enhanced graphite.

5. The gray cast iron composite material according to claim 4, characterized in that: The charge is prepared into a gray cast iron composition of: 3.20% carbon, 1.13% silicon, 0.98% manganese, 0.017% phosphorus and 0.065% sulfur, and the balance is iron.

6. The gray cast iron composite material according to claim 5, characterized in that: The molten metal is added with an inoculant of 0.5% of the weight of the molten metal, and the slag is removed after the molten metal is left still in the ladle for 3 minutes. The inoculant is a ferrosilicon inoculant containing 75% silicon and the remainder iron, and the particle size is 15 mm.

7. The gray cast iron composite material according to claim 6, characterized in that: The molten metal in the ladle is poured into the casting ladle in batches and subjected to secondary inoculation treatment. The inoculant is a ferrosilicon inoculant with a silicon content of 75% and the balance being iron. The particle size is 1.5 mm and the amount added is 0.1% of the weight of the molten metal.

8. The gray cast iron composite material according to claim 7, characterized in that: The chopped carbon fibers placed in the pouring cup of the casting are 1% of the weight of the casting.

9. The gray cast iron composite material according to claim 8, characterized in that: The pouring temperature of the molten metal is 1390°C.

10. The gray cast iron composite material according to claim 9, characterized in that: The gray cast iron has a tensile strength of 297 MPa.